The Influence of Marketing Mix and Students’ Sense of Belonging Mediated by Attitude on Purchase Intention for ITB Press Merchandise - Reyna Aszzura Rasyida; Atik Aprianingsih (Mandalika Institute, 2024)
Promotional merchandise has become a popular promotional tool in various sectors, including education. With more than twenty thousand students at each Indonesian university and high turnover each year, the market and potential demand remain highly promising. ITB Press, which are currently in their second year as the official merchandise seller for ITB, struggle with low sales and awareness among students. This indicates a need for improved market penetration. This study examines the predictors of purchase intention among their target market, which includes ITB students and alumni, focusing on 4Ps of marketing mix (product, price, place, promotion) and students’ sense of belonging, mediated by attitudes. A comprehensive quantitative approach with path analysis on SPSS was conducted to analyze the relationship between variables. By distributing questionnaires, 221 respondents consisting of ITB active students and alumni were gathered in this research. The findings show that, except for Place, all predictors significantly influence purchase intention, with attitudes serving as a mediating variable. The study reveals that ITB Press merchandise has a positive product perception among students. The primary motivation for purchasing merchandise is the students' pride and connection with ITB and the product itself, with most attention on the design, quality, and variety. Consequently, ITB Press should focus on creating appealing products that fit student preferences to maintain the positive perception, while maintaining a balance between price and promotions. This study highlights the importance of understanding the motivations and perceptions of both students and alumni, providing valuable insights for ITB Press to refine their marketing approach.